2009
DOI: 10.1145/1462055.1462058
|View full text |Cite
|
Sign up to set email alerts
|

Negative efficacy of fixed gain error reducing shared control for training in virtual environments

Abstract: Virtual reality with haptic feedback provides a safe and versatile practice medium for many manual control tasks. Haptic guidance has been shown to improve performance of manual control tasks in virtual environments; however, the efficacy of haptic guidance for training in virtual environments has not been studied conclusively. This article presents experimental results that show negative efficacy of haptic guidance during training in virtual environments. The haptic guidance in this study is a fixed-gain erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…If progress is not made in this area, however, there is a real danger that real-time VR feedback would become counterproductive if uninformed physical trainers use it to direct learners' attention to task-irrelevant features at inappropriate stages in learning (cf. Li et al, 2009;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If progress is not made in this area, however, there is a real danger that real-time VR feedback would become counterproductive if uninformed physical trainers use it to direct learners' attention to task-irrelevant features at inappropriate stages in learning (cf. Li et al, 2009;.…”
Section: Discussionmentioning
confidence: 99%
“…Tabata, Ueda, Kiyofuji, & Kuno, 2005;Drobny, Weiss, & Borchers, 2009). However, caution should be taken when using intuitively designed VR training environments, as it is clear that they may not always benefit motor learning, or reliably facilitate the transfer of motor skills from VR to more naturalistic settings (Li, Patoglu, & O'Malley, 2009). Addressing this issue, researchers have manipulated various practice components, such as virtual fixtures (Rosenberg, 1993), shared control and other haptic feedback mechanisms (Tzafestas, Birbas, Koumpouros, & Christopoulos, 2008), such as vibromotors attached to limbs that cue action within prespecified time constraints (Drobny & Borchers, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicate that haptic feedback, combined with visual feedback, can improve discrimination thresholds for low-frequency dynamic systems perceived passively, while discrimination of the dynamic behavior of actively excited systems does not show sensitivity to feedback modality. This finding will influence shared controller design depending on the approach selected (e.g., record and replay methods that require passive excitation [32], [33], [34] versus virtual fixtures or active shared controllers that require active excitation [4], [5], [7], [8], [31], [35], [36]). The method of excitation alone does not show a significant effect on discrimination ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed after-effects washed out after a short period of time. Error amplification strategies have been used successfully to speed up human motor learning of a dynamic task [6], [7], though error reduction in a dynamic target-hitting task showed negative training efficacy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the guidance hypothesis for shared control and other forms of haptic guidance [54]- [58]. A classical example of the guidance hypothesis for haptic guidance (in this case non-overridable physical feedback) is illustrated in Figure 2.…”
Section: Shared Control and The Guidance Hypothesismentioning
confidence: 99%